Incidence of delirium in hip fracture surgery at King Chulalongkorn Memorial Hospital - Sukhanonsawat, Siree; Thipakorn, Yanin; Thisayakorn, Paul (Chulalongkorn Medical Journal, 2022)
Background: Postoperative delirium in hip fracture patients is a significant public health problem that affects the quality of patients’ lives and increases morbidity and mortality rate. Objective: To investigate the incidence of delirium and associated factors in elderly patients who underwent hip fracture surgery. Methods: This is a cross-sectional descriptive study. Data were collected from the patients aged 65 years who underwent hip fracture surgery at King Chulalongkorn Memorial Hospital. The Thai Mental State Examination (TMSE) was used to investigate cognitive function preoperatively and on the 4th postoperative day. Postoperative delirium was assessed for 4 consecutive days using the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU). The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria for delirium was used to confirm the diagnosis. Results: There were 128 subjects recruited in the study; 92 women (71.9%), and 36 men (28.1%). Their mean age was 77.8 years. The study revealed that 21 patients (16.4%) developed postoperative delirium. Factors associated with delirium after hip fracture surgery were age, previous history of delirium, preoperative TMSE score 23, and delayed surgery exceeding 48 hours after admission. Conclusion: The incidence of postoperative delirium in elderly patients underwent hip fracture surgery at King Chulalongkorn Memorial Hospital was 16.4%. Age, previous history of delirium, low TMSE scores, and delayed surgery were associated with postoperative delirium.